2012
DOI: 10.2111/rem-d-11-00092.1
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Grazing and Yosemite Toad (Bufo canorus Camp) Breeding Habitat in Sierra Nevada Meadows

Abstract: Exclusion of cattle by fencing has been proposed to alleviate possible negative grazing impacts on hydrologic, water quality, and cover habitat conditions within Sierra Nevada meadows used by Yosemite toads (Bufo canorus Camp) for breeding. Our objectives were to: 1) determine associations between breeding pool habitat conditions and use of potential breeding pools by toads; and 2) determine how habitat conditions respond to cattle exclusion treatments on the Sierra National Forest, California. We randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…Our nutrient results are consistent with other examinations of surface water quality in similarly grazed landscapes. In the Sierra Nevada, Roche et al [14] found nutrient concentrations of surface waters within key cattle grazing areas (mountain meadows) to be at least an order of magnitude below levels of ecological or biological concern for sensitive amphibians. On the Wallowa-Whitman National Forest in northeastern Oregon, Adams et al [52] also reported nutrient levels to be at or below minimum detection levels in surface waters at key grazing areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our nutrient results are consistent with other examinations of surface water quality in similarly grazed landscapes. In the Sierra Nevada, Roche et al [14] found nutrient concentrations of surface waters within key cattle grazing areas (mountain meadows) to be at least an order of magnitude below levels of ecological or biological concern for sensitive amphibians. On the Wallowa-Whitman National Forest in northeastern Oregon, Adams et al [52] also reported nutrient levels to be at or below minimum detection levels in surface waters at key grazing areas.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the central Sierra Nevada, Myers and Whited [13] found FIB increased in surface waters below key grazing areas on USFS allotments following the arrival of cattle. However, Roche et al [14] found no evidence of degradation of Yosemite toad breeding pool water quality in key grazing areas on three allotments in the Sierra National Forest of central California. Examining land-use and water quality associations in watersheds throughout the Cosumnes River Basin, Ahearn et al [15] also reported water quality conditions in upper forested watersheds, which include USFS grazing allotments, to be well below levels of ecological concern.…”
Section: Introductionmentioning
confidence: 98%
“…Their paper also acknowledged that up to 82% of their study's stream sites (depending on which California Region water quality standard was applied) within grazing areas had violations of fecal coliform (California standards), rather than the E. coli (federal standards) [19]. Two other studies that looked at cattle impacts to river and forest wetl and habitats concluded that cattle had minimal effects on water quality and habitat conditions; however, these studies did not actually assess fecal contamination [20] [21]. Thus, for studies that did assessfecal contamination in streams associated with livestock presence, there is consistent evidence that cattle presence is associated with diminished stream water quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that livestock grazing has either mixed effects [24] or no negative effects on amphibians [25,26]. For example, studies conducted in northeastern Oregon showed no significant effects of moderate grazing on Columbia spotted frog ( Rana luteiventris ) reproduction and short-term survival [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies conducted in northeastern Oregon showed no significant effects of moderate grazing on Columbia spotted frog ( Rana luteiventris ) reproduction and short-term survival [25,27]. A companion study to our work examined Yosemite toad response to a gradient of livestock utilization in Sierra Nevada meadows and found no direct effect of grazing on Yosemite toad presence [26]. …”
Section: Introductionmentioning
confidence: 99%